M1-Type Macrophages Secrete TNF-α to Stimulate Vascular Calcification by Upregulating CA1 and CA2 Expression in VSMCs - Song X; Song Y; Ma Q; Fang K; Chang X (Dove Medical Press, 2023)
Xianqin Song,1 Yu Song,1 Quanping Ma,2 Kehua Fang,3 Xiaotian Chang1 1Medical Research Center of the Affiliated Hospital of Qingdao University, Qingdao, Shandong, People's Republic of China; 2Clinical Laboratory, The fourth People's Hospital of Jinan, Jinan, Shandong, People's Republic of China; 3Clinical Laboratory of the Affiliated Hospital of Qingdao University, Qingdao, Shandong, People's Republic of ChinaCorrespondence: Xiaotian Chang, Medical Research Center of the Affiliated Hospital of Qingdao University, Qingdao, Shandong, 266000, People's Republic of China, Tel/Fax +86 0532-82917331, Email changxt@126.comPurpose: Vascular calcification is a hallmark of atherosclerosis (AS). We and others confirmed that carbonic anhydrase I (CA1) and CA2 increased expression and catalyzed calcium deposition in atherosclerotic aortas. Macrophages have been demonstrated to be strongly related to AS. This study aimed to clarify how and which macrophage subtypes regulate CA1 and CA2 expression to stimulate aortic calcification.Methods and Results: THP-1 cells were induced to form M0, M1 and M2 macrophage subtypes. These cells and their culture supernatants were separately incubated with human vascular smooth muscle cells (VSMCs). Calcification was strongly increased in VSMCs treated with β-GP, a chemical inducer of cellular calcification, following incubation with M1 macrophages or their culture supernatants, and was much higher than that in VSMCs treated with β-GP alone. Meanwhile, the expression of CA1 and CA2, as well as calcification marker genes, including Runx2, BMP-2 and ALP, was increased in VSMCs during this process. TNF-α levels were also increased in the culture medium of M1 macrophages. M0 and M2 macrophages or their supernatants did not significantly stimulate calcification in VSMCs. Following transfection with anti-CA1 or CA2 siRNAs, β-GP-induced VSMCs showed decreased calcification, but the calcification level was partially increased when those VSMCs were incubated with the supernatants of M1 macrophages, while CA1 and CA2 expression as well as TNF-α levels were also elevated. When VSMCs were treated with TNF-α without β-GP induction, calcification and the expression of CA1 and CA2 were also significantly increased.Conclusion: The results of this study suggest that M1 macrophages can increase CA1 and CA2 expression to promote atherosclerotic calcification in VSMCs by secreting TNF-α.Keywords: atherosclerosis, calcification, carbonic anhydrase I, carbonic anhydrase II, macrophages, TNF-&#x03B1